(untitled) (Research, Society and Development, 2020)
This paper aims to discuss the importance of fieldwork as a methodological resource in the context of the teaching and learning process and in Geography classes. In order to put into practice the knowledge acquired in the classroom, fieldwork with 7th grade students (B), from the Judith Barbosa de Paula Rego Elementary School, located in the city of Queimadas-PB, was used as methodology. The results demonstrate that the theoretical classes accompanied by practical classes in the field provide a greater performance in learning. There was an increase in grades, where it was possible to observe that from the fieldwork students had a greater interest in studying the geographic sciences, leaving the abstract to the experienced they had the opportunity to associate what they already knew from their daily information with the contents of Geography seen in the classroom. The development of works with the field class allows the articulation between theory and practice, as well as a way to aggregate the students’ knowledge with the knowledge of the textbook, which is extremely important in the teaching-learning process.